The Effect of Turmeric-based Vaginal Liquid Soap with Different Concentrations on the Incidence of Vaginal Discharge and PH : Experimental Test on Santriwati of Darussholah II Islamic Boarding School North Pontianak - Lutfiawaliah, Delvia; Fatmasari, Diyah; Arwani (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: As many as 90% of Indonesian women have the potential to experience vaginal discharge because of Indonesia's tropical climate. Hot and humid weather causes mold to easily develop and cause vaginal discharge in women. For this reason, there needs to be an innovation that can be used as one of the efforts to overcome vaginal discharge in general. The purpose of this study is to prove the potential of turmeric-based vaginal soap that is able to overcome vaginal discharge. Subjects and Method: This was a quasi experiment study. The study was conducted at the Darussholah II Islamic Boarding School, North Pontianak, Indonesia from November to December 2023. The sample was divided into 3 groups: (1) , namely groups 1, 2 and 3 with 5%, 10%, and 15% turmeric liquid soap interventions. The dependent variables studied were vaginal discharge and vaginal ph, and the independent variable was Vaginal Turmeric Soap. The analysis technique uses Wilcoxon bivariate analysis. Results: The average value of 5% soap whiteness reduction was 0.96+0.20, 10% was 0.88+0.33 and 15% was 0.92+0.27 with a p value of 0.585. The average value of the pH reduction of 5% soap was 0.60 + 0.57, 10% soap was 0.52 + 0.65, and 15% soap was 0.48 + 0.65 with a p value of 0.904. At a dose of 5%, the reduction in vaginal discharge and pH was the highest compared to other groups. And the results of the analysis showed that the administration of 5%, 10%, and 15% doses did not have a significant difference in changes in vaginal discharge and pH. Conclusion: A 5% dose of turmeric-based vaginal soap was more effective at treating vaginal discharge and lowering vaginal pH, compared to other groups in this study. It is hoped that young women will be more selective in choosing soap in maintaining pH and vaginal discharge, especially if used for a long period of time.